UKRAINIAN ELITES STRATEGIES TO DONBAS: «BIG DATA»-RESEARCH OF THE FACEBOOK NATIONAL SEGMENT - A. A. Tokarev (Vestnik MGIMO-Universiteta)
The conflict in the South-East of Ukraine has acquired a protracted nature, what is significantly affected by three main factors. 1) The main actors of the conflict (Ukraine, DPR/LPR, Russia, USA, OSCE) have in principle different opinions about its resolution/escalation. Secondly, despite the recognition of the DPR/LPR territory belonging de jure to Ukraine by majority of actors, the basic document "Minsk-2" uses by the discursive, but not a real support of the actors. Third, Ukraine does not have a consolidated position in the national community and elites concerning the Donbass. Fourth, contrary to the technical, economic, and military support for the region by Russia the official Kiev is the main promoter of secession in Donbas by means of ATO, in spite of the public discourse about the need to reintegrate these territories. Research question: what strategy for the Donbass are shared by Ukrainian elites? Methodological basis: analysis of the Ukrainian Facebook network segment with a combination of quantitative (Big Data) and qualitative (in-depth interviews) methodology. Results: the topic of Donbass in general very poorly presented on the pages of top Ukrainian bloggers in Facebook. The test content is mainly Russian-speaking, Russia is mentioned more often than Donbas. The US and Europe occupy roughly equal positions in the public discourse on the number of references. In the array of almost 90 000 posts in the first 10 months of 2016 only 6% relate to the region of Donbass. Number of posts that contain not the strategic vision of the Donbass future, but only mention of it, is less than half-percent. As a result of manual processing of data, the author comes to the key findings - Ukrainian elites have no the consensus strategy for the Donbass, but strategies to froze the conflict and to conquer of Donbass compete one to each other. The region is not perceived like an object for which Ukraine should fight not only for the territory, but also the people. In conclusion author presented the later iterations which are necessary to improve the degree of verification of the findings in the new study.